EVALUATING THE ROLE OF STRATEGIC LEADERSHIP IN THE SUCCESS OF CORPORATE DIGITAL TRANSFORMATION - Ahmad Kasyfi Ali (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2024)
In today’s rapidly evolving digital landscape, strategic leadership plays a decisive role in determining the success or failure of corporate digital transformation initiatives. This study explores the relationship between strategic leadership and the effectiveness of digital transformation across various industries. Motivated by the high failure rate—nearly 70%—of digital initiatives due to poor leadership, this research employs a mixed-methods design that combines qualitative interviews and quantitative surveys. The qualitative component involves in-depth interviews with organizational leaders who have overseen digital transitions, while the quantitative survey gathers data from over 100 companies using structured instruments to evaluate leadership effectiveness, employee engagement, and transformation outcomes. The findings reveal that organizations led by strategic leaders are 25% more likely to succeed in digital initiatives. These leaders cultivate innovative cultures, align digital strategies with corporate goals, and foster high employee engagement—factors that directly impact transformation performance. Case studies from companies such as Microsoft, Adobe, and General Electric illustrate how visionary leadership accelerates adaptation and innovation. Conversely, companies like Kodak and Blockbuster demonstrate the consequences of leadership failure in responding to digital disruption. This study concludes that strategic leadership is not a supportive element but a foundational driver of digital transformation. Effective leadership entails vision, adaptability, emotional intelligence, and the capacity to lead cultural change. The research contributes to leadership theory and offers practical recommendations for organizations navigating digital challenges. Future research should further investigate long-term impacts of strategic leadership on organizational resilience and innovation sustainability.